2016
DOI: 10.1002/eco.1792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating mountain meadow groundwater response to Pinyon‐Juniper and temperature in a great basin watershed

Abstract: This research highlights development and application of an integrated hydrologic model (GSFLOW) to a semiarid, snow-dominated watershed in the Great Basin to evaluate Pinyon-Juniper (PJ) and temperature controls on mountain meadow shallow groundwater.The work used Google Earth Engine Landsat satellite and gridded climate archives for model evaluation. Model simulations across three decades indicated that the watershed operates on a threshold response to precipitation (P) >400 mm/y to produce a positive yield (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The importance of interflow to support down-gradient consumption in the lower portions of CC is supported by other studies in which increased above ground productivity (Swetnam et al, 2017), soil carbon stocks (Perdrial et al, 2018), and hydrologic vegetation gradients (Hwang et al, 2012) are observed in downslope, convergent topography. Monsoon rains also support late summer productivity (Berkelhammer et al, 2017), and it is theorized that a weak monsoon may result in high groundwater use by phreatophytes (Carroll et al, 2017) and a reduction in late summer stream flow. Our results support the hypothesis presented by others (Carroll et al, 2018;Cowie et al, 2017;Zhang et al, 2018) that the upper subalpine dominates groundwater recharge in mountain systems.…”
Section: What Controls Spatially Distributed Groundwater Recharge?mentioning
confidence: 99%
“…The importance of interflow to support down-gradient consumption in the lower portions of CC is supported by other studies in which increased above ground productivity (Swetnam et al, 2017), soil carbon stocks (Perdrial et al, 2018), and hydrologic vegetation gradients (Hwang et al, 2012) are observed in downslope, convergent topography. Monsoon rains also support late summer productivity (Berkelhammer et al, 2017), and it is theorized that a weak monsoon may result in high groundwater use by phreatophytes (Carroll et al, 2017) and a reduction in late summer stream flow. Our results support the hypothesis presented by others (Carroll et al, 2018;Cowie et al, 2017;Zhang et al, 2018) that the upper subalpine dominates groundwater recharge in mountain systems.…”
Section: What Controls Spatially Distributed Groundwater Recharge?mentioning
confidence: 99%
“…However, to our knowledge, few modeling studies have considered the impacts of climate change coupled with changes in vegetation (Buma and Livneh, 2015;Carroll et al, 2017;Pribulick et al, 2016). In this study, we incorporated changes from the CMIP5 dynamic vegetation models and from an estimate of forest mortality (McDowell et al, 2016) to consider the impacts of both climate and vegetation changes on the water balance in a headwater system of the CRB, the San Juan River basin.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, field observations and conceptual and numerical models of GDEs developed using traditional hydrogeologic approaches can provide important context and constraints for interpreting remotely sensed time‐series data (Carroll et al. ). Field assessments of the hydrogeologic controls on spring locations and discharge rates integrate information on the lithology, stratigraphy, geomorphology, and topography associated with springs.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of hypothesized physical mechanisms supporting spring resilience (e.g., spring microclimates, recharge zone dynamics, and subsurface hydrogeology) can benefit from the integration of remote-sensing metrics with other lines of evidence derived from field studies (P erez Hoyos et al 2016). In particular, field observations and conceptual and numerical models of GDEs developed using traditional hydrogeologic approaches can provide important context and constraints for interpreting remotely sensed time-series data (Carroll et al 2017). Field assessments of the hydrogeologic controls on spring locations and discharge rates integrate information on the lithology, stratigraphy, geomorphology, and topography associated with springs.…”
Section: Integrated Approaches To Identify Possible Hydrologic Refugimentioning
confidence: 99%